(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A straightforward and reproducible technique known as "Green Chemistry" yields nanoparticles with improved stability and high dispersion in an aqueous solution. Plant extracts, bacteria, fungi and algae can all be used to synthesize nanoparticles. A popular medicinal mushroom with unique biological qualities, Ganoderma lucidum has antibacterial, antifungal, antioxidant, anti-inflammatory, and anticancer effects. In this study, AgNO3 was reduced to produce silver nanoparticles (AgNPs) using aqueous mycelial extracts of Ganoderma lucidum. The hence synthesized nanoparticles on phytofabrication exhibited the presence of alkaloids, flavonoids, saponins and cardiac glycosides. Tested against strains of both Gram-positive and Gram-negative bacteria, the synthesized nanoparticles’ antibacterial efficacy was determined. The pathogens were effectively inhibited by the silver nanoparticles, lowering the risk to the environment and public health in the process.